Pengaruh Pelapisan Nikel pada Tool End Mill HSS Terhadap Nilai Kekerasan dan Temperature Proses Milling Alumunium 6061 - Sifa, Agus; Endramawan, Tito; Sukardi, Casiman; Aryadi, Haerul (Politeknik Negeri Indramayu, 2023)
The machining process of dry machining milling method is a machining process without additional coolant, but this method has several problems during the process and after the machining process, namely Tool temperature can easily rise and has a major impact on tool wear, so the purpose of this research is to develop a dry machining method with variations tools that are coated with nickel, by utilizing the properties of nickel material that can withstand heat and corrosion, therefore a nickel coating is used on the tool which will affect the temperature parameters of the tool. The coating method that will be carried out is the electroplating method. This method is a metal coating method which is often called electrodeposition, or the process of depositing the coating metal on the base metal using electrolysis. This research was carried out using experimental testing methods to obtain tool temperature parameters and hardness on the tool coating. The voltage used in the electroplating process is 6 V/ 0.7 A for 5, 10, and 15 minutes to produce a nickel layer thickness of 0.024 mm in 15 minutes, so every 5 minutes the layer is 0.08 mm. The experimental testing process used the HSS tool Ø 12 / 4 F and a aluminum 6061 workpiece which resulted in an intermediate temperature that was not coated with nickel (uncoated) at 3 mm feeding spindle speed 3000 rpm the temperature reached 73.6 ºC while that which was coated with nickel (coated) the temperature only reached 58.6 ºC, and get an average hardness value on the nickel layer, which is 279.9 Hv